An evaluation of the program on enhancing resilience to natural disasters and the effects of climate change in Bangladesh - Hernandez, Ricardo; Ahmed, Akhter; Akter, Arifeen; Hossain, Nusrat Zaitun; Choudhury, Samira; Malek, Mehrab (International Food Policy Research Institute, 2016)
The overall objective of the ER+ component is to assist ultra-poor women and their families in disaster-prone areas of Bangladesh in lifting themselves above the lower poverty line toward greater food security. To achieve the objective, a third “promotional” year has been introduced to ER, during which women—either ER laborers/trainees themselves or the wives, daughters, mothers, or sisters of male ER laborers/trainees—receive a substantive cash grant to invest in a productive asset or income-generating activity in combination with relevant business-related training, a one-year monthly cash allowance, and intensive follow-up support. The resulting model therefore combines the pre-existing “protective” elements (employment generation and 4 community asset development) with “promotional” elements for a more viable pathway out of extreme poverty and toward food security